OPTIMIZATION OF THE COMPOSITION OF THE INSULATING MATERIAL "HEATISOL-2" ON THE BASIS OF CULLET AND WASTE INDUSTRY - Goncharenko, O. O. (Science and Transport Progress, 2005)
This article describes conceptional approach to the organization of production and manufacturing technique of the insulative material «Heatisol-2» and gives general information on the new material.